`i, (x^2+x)^2 +3.(x^2+x)+2` phân tích đa thức thành nhân tử

`i, (x^2+x)^2 +3.(x^2+x)+2`
phân tích đa thức thành nhân tử

2 bình luận về “`i, (x^2+x)^2 +3.(x^2+x)+2` phân tích đa thức thành nhân tử”

  1. Giải đáp:
    ( x^2 + x + 1 ) (x^2 + x + 2 )
    Lời giải và giải thích chi tiết:
      ( x^2 + x)^2 + 3 (x^2 + x ) + 2
    Đặt t = x^2 + x ta có 
      t^2 + 3t + 2
    = t^2 + t + 2t + 2
    = t ( t + 1 ) + 2 ( t + 1 )
    = ( t + 2 ) (t+1)
    Thay t = x^2 + x ta có 
    ( x^2 + x + 1 ) (x^2 + x + 2 )

    Trả lời

Viết một bình luận

Câu hỏi mới